Health literacy among first-generation Italian immigrants in Norway. (30th September 2020) - Terragni, L; Calogiuri, G; Finbråten, H
Abstract: Background: People with an immigration background often have poorer health than the general population. Italians in Norway have tripled throughout the past 15-years, but little is known about their health. Health literacy (HL) has been emerging as a fundamental construct in enabling citizens to play an active role in improving their own and theirs community's health. The objective of our study was i) to describe HL among first-generation Italian immigrants in Norway, ii) examine the association between HL and health-related empowerment, and iii) compare HL in Italian immigrants with the general Norwegian population's. Methods: The data was retrieved from a cross-sectional survey (n = 321) conducted within the study Mens Sana in Corpore Sano (inclusion criteria: age ≥18 years, living in Norway permanently, having lived in Italy at least until age 16). HL was measured using the short form of the European Health literacy survey questionnaire (HLS-Q12; α = 0.83). Empowerment was assessed using a 4-items scale (α = 0.73), developed on basis the World Health Organization's definition of individual empowerment and aspects of patient empowerment. Additionally, information about gender, age, educational level, and self-rated health was collected. Results: Preliminary results indicated that 8% had inadequate HL, whereas about 40% had marginal HL. No significant differences in HL were observed in relation to gender, age, education level or general health. A medium correlation was found between HL and empowerment (r = 0.42, p < 0.001). The Italian's HL was significantly lower than the general Norwegian population's (M±SD = 32.46±4.79 and 33.11 ± 4.12, respectively; p = 0.028). Conclusions: This is the first study investigating HL and its associations with the health-related empowerment of first-generation Italian immigrants in Norway. More research is needed in order to better understand this phenomenon as well as the effectiveness of HL-enhancing initiatives. Key messages: We investigated the levels of health literacy and health-related empowerment among first-generation Italian immigrants in Norway. The Italians' heath literacy, which correlated with empowerment, was lower than the general Norwegian population's. There were no differences across gender, age, education level or general health.